Utilizing Magnetic Building Blocks as A Learning Medium to Enhance Creativity in Early Childhood (Qualitative Case Study at ABA 2 Kindergarten, East Ungaran, Semarang Regency) - Musyarofah, M; Asmawulan, Tri (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: This study aims to analyze the use of Magnetic Building Blocks as a learning medium to enhance creativity in early childhood. This research is motivated by the critical need to stimulate creativity from an early age through constructive, educational, and enjoyable play activities.Methodology: This study uses a qualitative approach with a case study design. This research was conducted at ABA 2 Kindergarten in East Ungaran with 15 Group B children aged 5-6 years in the 2025-2026 academic year. Data were collected through participant observation, semi-structured interviews with teachers and parents, and documentation of children's work.Results: The findings indicate that the use of Magnetic Building Blocks significantly improved all six aspects of children's creativity: ideational fluency, originality, flexibility, elaboration, problem-solving, and persistence. Children became more active, independent, and demonstrated higher-order creative thinking. They demonstrated increased courage in expressing original ideas, adapting their strategies, and persevering in completing tasks.Application/Originality/Value: This study concludes that the Magnetic Building Blocks Game is an effective and innovative learning medium for stimulating creativity in early childhood. It provides empirical evidence of its application in real-life educational settings, offering a practical alternative for kindergarten institutions to implement a constructive, play-based learning approach that encourages holistic creative development. This medium is recommended as a valuable tool for educators seeking to create meaningful and engaging learning experiences.